Enhanced mechanical properties of AA7075 alloy through friction stir processing: a review - Patil, Tukaram; Washimkar, Dinesh; Pawar, Ashish; Naidu, Mithul; Shinde, Sachin; Salunkhe, Sachin (Frontiers in Mechanical Engineering, 2025)
A friction stir-based material processing technique for improving the surface and microstructural characteristics of materials is called friction stir processing (FSP). Because FSP involves severe deformation caused by plasticity, material flow, heat transport, and microstructure evolution, it is a multi-physics problem that can be difficult to describe. The performance of the friction stir process is influenced by several factors, including plastic deformation, material flow, temperature, and residual stresses. Enhancing the process requires developing a numerical model that considers these influencing parameters for a specific workpiece material.Lightweight materials such as aluminum alloys offer high specific strength and ductility, making them ideal for applications in the automotive and aerospace industries. Today’s industries are primarily interested in metallic alloys that are lightweight and strong. Because of their low weight, aluminum alloys hold a special place in the industry. Much effort is being made to improve the mechanical qualities of aluminum through a surface modification technique called FSP. This study reviews the literature on the FSP of the AA7075 alloy, focusing on the influence of key parameters such as rotational speed, traverse speed, and machining conditions. Modeling and simulations of FSP for material change have not been extensively studied. This study uses ABAQUS/Explicit to create a computationally efficient process model based on the coupled Eulerian–Lagrangian (CEL) formulation to simulate the FSP of aluminum alloy. Tool plunging, dwelling, and stirring phases are all included in the simulation of the full FSP process using the three-dimensional (3D) finite-element model. The impact of tool rotational speed and tool pin profile during the FSP process is assessed using simulations. Comparing the proposed model’s computational efficiency to that of other models currently in use for friction stir welding procedures is another way to assess its effectiveness. To validate the model, the FSP experiment is conducted using temperature and process force measurements. This work shows that the CEL model can be a useful numerical tool for simulating complex process mechanics and optimizing FSP process parameters for industrial applications.